Research of generators of impulses for electrotechnological installations with solutions of electrolytes - E.A. Yakovlev; A.D. Mekhtiyev; V.V. Yugay; L.A. Zinovyev (Қарағанды университетінің хабаршысы. Физика сериясы)
Article is devoted to functioning of pulse electrotechnological installations on low frequency (0,1 Hz) and industry frequency. As an analog schemes of pulse relaxation generators for processes of electric erosion machining of metals are considered. Аlso RC-generators and static generators of impulses (transformers of the industry frequency with the gate) were considered. Pulse RC-generators on voltage of 1000 V and a pulse repetition rate of 0,1 Hz and the static generator of impulses on voltage of 1000 V and a pulse repetition rate of 50 Hz are developed. Experiments on studying of development of the partial (sliding) electric discharge with attenuation at the 1st stage and with transition to the second stage are made. Experiments on studying of a complete and incomplete electrical breakdown of electrolytes are also made. An analogy was found between the course of the discharge in the electrolyte and the surface of a solid dielectric covered with a thin film of electrolyte. In both cases, discharges first develop in the form of a pre-discharge current of small magnitude, and end with a transition to a high-current discharge (breakdown). It is shown that the measured delay time of electric discharge (4 microsec) much less a delay time of the electrothermal category (30 microsec). Owing to this fact breakdown in this case has to be it is carried rather to electric, than to a thermal look.